PROSES REGISTRASI RAWAT JALAN VIA SMS STUDI KASUS PADA PASIEN RAWAT JALAN RSUD DELI SERDANG LUBUK PAKAM TAHUN 2018 - Yulia Mehatte; Myrnawati; Karnirius Harefa; Bahdin Nur Tanjung; Mestika Lumbantoruan (Excellent Midwifery Journal, 2024)
The hospital as one of the health service subsystems that organizes two types of services for the community, namely health services, and administrative services. Hospital is one of the organizations that provide health services to the community. To be said well, the hospital must meet the basic requirements that have been determined, while the basic requirements of a health service can be said to be both available and continuous (acceptable and continuous), acceptable and reasonable (acceptable and appropriate), easily accessible, affordable and quality. The purpose of this study was to determine the outpatient registration process vVia SMS at Deli Serdang Lubuk Pakam Hospital. This type of research uses descriptive qualitative case study method, conducted at Deli Serdang Lubuk Pakam Hospital in March to September 2019, informants in this study amounted to 7 people, the method of data collection using In-dept Interview. From the results of the study showed the outpatient registration process Via SMS was going well, visitors gave a good perception, the disadvantages of this method were not found, the advantages of this method were found, there were found inhibiting factors, and there were found supporting factors from the outpatient registration process via Texting at Deli Serdang Lubuk Pakam Hospital. Conclusion: this process has been going well, it is expected to the Hospital to promote this process so that all visitors can apply this method in registering for outpatient treatment.